UXUC - User experience & urban creativity scientific journal, vol.2, nº2 (Dez. 2020) - Neves, Pedro Soares (2021)
On the 2020 conference was in fact proven that the consistency of knowledge and structure of thought in the several disciplinary areas regarding the urban creativity topics, are giving way to multiple approaches to classes integrated in master courses, informing the teaching of art historians, the work of designers, and research of cognitive scientists and educators. It was evident that this trend will continue in multiple forms including experimental ones bridging theory and practice, sometimes inverting the role of researchers and authors, but always enlarging audiences, practitioners and studious. On this issue you can observe how the relation evolved between UX (User Experience) and Urban Creativity topics.